Vibration isolation and damping using a piezoelectric flextensional suspension with a negative capacitance shunt. (June 2020) - Billon, K.; Montcoudiol, N.; Aubry, A.; Pascual, R.; Mosca, F.; Jean, F.; Pezerat, C.; Bricault, C.; Chesné, S.
Highlights: The main objective of this study is reduce vibration transmission. A piezoelectric suspension using a mechanical amplifier is developped. An equivalent electrical model is built to optimize different shunts. A comparison is made with a conventional viscoelastic suspension. Finally, the device is tested experimentally. Abstract: A suspension combining a piezoelectric component and a mechanical amplifier is studied in view to reducing vibration transmission over a wide frequency band. The principle and design of the piezoelectric suspension are approached using electromechanical and finite element models. The aim is to combine high damping at resonant frequency and high isolation at high frequency. The electromechanical coupling of the transducer allows implementing mechanical damping and electric damping with different shunts based on resistive and negative capacitance. The first design of the device is tested experimentally.